Information, Animal Spirits, and the Meaning of Innovations in Consumer Confidence - Barsky, Robert B; Sims, Eric R (American Economic Review, 2012)
Innovations to consumer confidence convey incremental information about economic activity far into the future. Does this reflect a causal effect of animal spirits on economic activity, or news about exogenous future productivity received by consumers? Using indirect inference, we study the impulse responses to confidence innovations in conjunction with an appropriately augmented New Keynesian model. While news, animal spirits, and pure noise all contribute to confidence innovations, the relationship between confidence and subsequent activity is almost entirely reflective of the news component. Confidence innovations are well characterized as noisy measures of changes in expected productivity growth over a relatively long horizon. (JEL D12, D83, D84, E12)